Pengaruh Model Pembelajaran STAD Berbantuan Media Monopoli Ragam Budaya Terhadap Hasil Belajar IPS Siswa Kelas 4 SD N Gunungsari - Anggraeni Ratna Purnasiwi (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This study aims to examine the effect of the STAD learning model assisted bymulticultural monopoly media on social studies learning outcomes for 4th grade studentsof Gunungsari State Elementary School. This study uses an experimental method with theresearch design used is a pre-experimental one group pre-test - post-test design. Theresearch subjects were 4th grade students of SD Negeri Gunungsari. The sample in thisstudy amounted to 15 students. Data collection techniques used are multiple choice testsand documentation.The results showed that the hypothesis test using the Wilcoxon testshowed that the Asymp value. Sig is <0.001. So, because sig < 0.005, Ho is rejected whileHa is accepted, which means that there is an influence of the STAD learning model assistedby the monopoly of cultural diversity on the social studies learning outcomes of 4th gradestudents of Gunungsari State Elementary School. It is shown by the existence of students'interest in learning media and the attitude of cooperation between groups that affectstudents' social studies learning outcomes which increase. This is an evaluation foreducators that applying learning models and media can affect student learning outcomes.